A PRAGMATIC ANALYSIS OF MAXIM VIOLATIONS IN SENSATIONALIZED DIGITAL NEWS ON ARTISTS - Nur Fadillah; Fatimah Hidayahni Amin; Geminastiti Sakkir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
The phenomenon of sensationalism in digital news about celebrities is increasing as online media compete to attract readers’ attention. To gain clicks and audience engagement, media often use ambiguous and hyperbolic language that has the potential to violate pragmatic principles. This study aims to identify forms of maxim violations in sensational digital news about celebrities, analyze how they are implemented by the media, and examine their impact on public perception. This study uses a qualitative method with a discourse analysis design. The research data consists of fifteen digital news stories with the theme of celebrity sensationalism taken from five popular online news portals in Indonesia. Data analysis was carried out using Levinson’s pragmatic heuristic theory, which includes the Q-Heuristic, I-Heuristic, and M-Heuristic, and analyzed through the interactive model of Miles, Huberman, and Saldaña (2014). The results of the study indicate that violations of the M-Heuristic were the most dominant, followed by the I-Heuristic and Q-Heuristic, which are used as discourse strategies to create drama and sensational effects. The impacts include reader misunderstanding, reinforcement of negative stereotypes about artists, and decreased media credibility.